2014
DOI: 10.1371/journal.pone.0112424
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cells Provide a Notch-Dependent Pro-Tumoral Niche for Enhancing Breast Cancer Survival, Stemness and Pro-Metastatic Properties

Abstract: Treating metastasis has been challenging due to tumors complexity and heterogeneity. This complexity is partly related to the crosstalk between tumor and its microenvironment. Endothelial cells -the building blocks of tumor vasculature- have been shown to have additional roles in cancer progression than angiogenesis and supplying oxygen and nutrients. Here, we show an alternative role for endothelial cells in supporting breast cancer growth and spreading independent of their vascular functions. Using endotheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 51 publications
0
68
0
1
Order By: Relevance
“…Generally, increase in glucose metabolism and lactate production correlates with the increased proliferation rate of the cancer cells. Previously we reported that endothelial cells enhance proliferation capacity of cancer cells 4 days after co-culture was established12. Accordingly, the metabolic alterations identified in the first 48 hours might be solely associated with the cancer–endothelial-cells interactions and not with proliferation of cancer cells.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Generally, increase in glucose metabolism and lactate production correlates with the increased proliferation rate of the cancer cells. Previously we reported that endothelial cells enhance proliferation capacity of cancer cells 4 days after co-culture was established12. Accordingly, the metabolic alterations identified in the first 48 hours might be solely associated with the cancer–endothelial-cells interactions and not with proliferation of cancer cells.…”
Section: Discussionmentioning
confidence: 83%
“…We previously established an in vitro model consisting of co-culture of cancer and endothelial cells111213. We selected endothelial cells E4 + EC previously created by transfection of the Primary Endothelial Cells (PECs) with the adenoviral E4ORF1 gene14.…”
mentioning
confidence: 99%
“…described that TEC convert indolent tumor cells to more aggressive cells with greater tumorigenicity, extranodal invasion, and chemoresistance . Moreover, other groups have also demonstrated that the Notch signals in EC are involved in tumor progression and stem cell phenotype . Notch activation in EC promotes tumor cell migration and metastasis along with neutrophil infiltration …”
Section: Role Of Tumor Endothelial Cells In Tumor Progression and Metmentioning
confidence: 99%
“…(42,43) Moreover, other groups have also demonstrated that the Notch signals in EC are involved in tumor progression and stem cell phenotype. (44)(45)(46)(47) Notch activation in EC promotes tumor cell migration and metastasis along with neutrophil infiltration. (48) In addition to the production of factors that simulate tumor cell progression, TEC also downregulate tumor suppressive factors.…”
Section: Role Of Tumor Endothelial Cells In Tumor Progression and Metmentioning
confidence: 99%
“…They also found that MBG could downregulate certain genes involved in adhesion in the endothelial monolayers obtained from the human brain. Since tumor endothelial cells have been found to be associated with cancer progression and metastasis [26,27], the findings mentioned above could indicate a connection between MBG and glioma malignancy. Furthermore, it is known that MBG is involved in the inhibition of the sodium pump [28].…”
Section: Introductionmentioning
confidence: 95%